2014
DOI: 10.1074/jbc.m114.605394
|View full text |Cite
|
Sign up to set email alerts
|

The Human Antimicrobial Peptide LL-37 Binds Directly to CsrS, a Sensor Histidine Kinase of Group A Streptococcus, to Activate Expression of Virulence Factors

Abstract: Background: Group A Streptococcus responds to the human antimicrobial peptide LL-37 by up-regulating virulence factors controlled by the CsrRS system. Results: We provide genetic and biochemical evidence for direct binding between LL-37 and the CsrS receptor. Conclusion: LL-37 signaling through CsrS is mediated by a direct binding interaction. Significance: These findings advance our understanding of streptococcal virulence regulation in response to a host signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…We also found that a plasmid-expressed RocA variant consisting of only the membrane-spanning domains is sufficient to complement a rocA mutant strain, consistent with RocA indirectly enhancing CovR phosphorylation. Finally, we also discovered that the inhibition of CovS activity by the antimicrobial peptide LL-37 (35) does not occur in strains that lack or overexpress RocA, adding evidence that RocA functions by modulating CovS activity. The virulence consequences of functional or mutant rocA alleles are discussed, with particular reference to how the natural rocA mutation in M3 GAS isolates may influence the association of this serotype with severe invasive infections.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We also found that a plasmid-expressed RocA variant consisting of only the membrane-spanning domains is sufficient to complement a rocA mutant strain, consistent with RocA indirectly enhancing CovR phosphorylation. Finally, we also discovered that the inhibition of CovS activity by the antimicrobial peptide LL-37 (35) does not occur in strains that lack or overexpress RocA, adding evidence that RocA functions by modulating CovS activity. The virulence consequences of functional or mutant rocA alleles are discussed, with particular reference to how the natural rocA mutation in M3 GAS isolates may influence the association of this serotype with severe invasive infections.…”
mentioning
confidence: 81%
“…Mg 2ϩ and the amphipathic antimicrobial peptide LL-37 function as ligands for CovS (38,39). At subinhibitory concentrations (e.g., concentrations at which no antibacterial action is observed), LL-37 binds to CovS and inhibits CovRS-mediated regulation, while Mg 2ϩ has opposing activity and enhances CovRS-mediated regulation (35). Given our previous data showing that RocA directly or indirectly functions through CovRS (24), we reasoned that RocA may modify the ability of Mg 2ϩ and/or LL-37 to regulate CovRS activity.…”
Section: Figmentioning
confidence: 99%
“…Because multiple stress conditions promote CovS Spy phosphatase activity, it was proposed that CovS Spy is responsive to general stresses affecting membrane structure [164]. On the other hand, there is also evidence that CovS Spy activities are modulated by specific external ligands, including Mg 2+ , but not other divalent cations, and the human antimicrobial peptide LL-37 at subinhibitory concentrations, but not other antimicrobial peptides [165168]. CovR Spy is also phosphorylated at the threonine residue T-65 by an STK [145,169], similar to CovR Sag of S. agalactiae [170].…”
Section: Signals That Activate Covrs or Orphan Regulator Covrmentioning
confidence: 99%
“…One possible factor contributing to the decrease in LL-37 activity is that the cations of specific antimicrobial peptide interact with mucin anions, which is a component of airway mucus, resulting in a decrease in the antimicrobial activity of LL-37 [30]. It was found that LL-37 induces the virulence of Streptococcus of group A due to increased production of virulence factors, which is mediated by the component of the regulatory system CsrRS [31]. In year 2014 J.J. Velarde and coauthors identified the smallest fragment of LL-37-RI-10 required for binding to CsRS.…”
Section: Resultsmentioning
confidence: 99%
“…In the opinion of I. Gryllos and coauthors (2008), LL-37 has a paradoxical effect, stimulating the regulated CsrRS expression of the virulence gene, thereby increasing the pathogenicity of group A Streptococcus during an infectious disease. The ability of Streptococcus of group A to perceive and respond to LL-37 may partially explain the susceptibility of humans as a biological species not only to Streptococcus of group A, but also to streptococcal infection in general [31]. Based on the data obtained, it was suggested that in the conditions of LL-37 deficiency an inversion of its action is observed, that is, instead of the expected bactericidal effect, the virulence of the microorganism increases [35].…”
Section: Resultsmentioning
confidence: 99%